The Role of Financial Literacy, Financial Knowledge and Financial Attitudes on Financial Management Behavior: Study of the Fisheries Industry in Ambon, Indonesia - Loppies, Lilian Sonya (HM Publisher, 2023)
In the fishing industry, financial management behavior can involve decisions related to managing revenue from fish sales, optimizing operational costs, and planning for long-term sustainability. This study aimed to determine the role of financial literacy, financial knowledge and financial attitudes on financial management behavior. This study is research with a quantitative approach and uses primary data obtained from a survey process using a questionnaire, where the survey process was carried out online. The independent variable in this study is financial management behavior (Y). The dependent variable in this study is financial literacy (X1), financial knowledge (X2), financial attitudes (X3). The study results show that there is a significant relationship between financial literacy and financial knowledge, p=0.000. The study results also show that there is a significant relationship between financial knowledge and financial attitudes, p=0.000. The study results also show that there is a significant relationship between financial attitudes and financial management behavior, p=0.000. In conclusion, financial literacy plays a role in increasing financial knowledge. Financial knowledge plays a role in improving financial attitude. Financial attitude plays a role in improving financial management behavior in the fishing industry in Ambon, Indonesia.